Clinical Characteristics and Aetiological Factors of Ludwig’s Angina: A Hospital-Based Study (Bangladesh Journal of Otorhinolaryngology, 2026)
Background: Ludwig’s angina is a rapidly progressive cellulitis of the submandibular and sublingual spaces that can lead to airway compromise. Identifying its clinical features and aetiology is crucial for timely management.Objective: The study aimed to evaluate the clinical features of Ludwig’s angina and their association with aetiology and patient clinical Characteristics.Methods: A hospital-based cross-sectional study was conducted from January to 30 June 2014 in the Departments of Otolaryngology and Head–Neck Surgery at Dhaka Medical College Hospital, Sir Salimullah Medical College & Mitford Hospital, and Shaheed Suhrawardy Medical College Hospital. A total of 50 patients clinically diagnosed with Ludwig’s angina and admitted to the respective departments were included using purposive sampling. Patients with other causes of neck swelling (e.g., lymphangioma, haemangioma, cystic hygroma, lymphoma, submandibular gland neoplasm) were excluded.Results: The mean age was 34.8±17.7 years, with the highest proportion (24%) in the 31– 40 years age group. Most patients were male (72%), from lower socioeconomic status (70%), and rural areas (82%). All patients presented with neck swelling and pain; fever (90%) and dysphagia (72%) were common. Dental infection was the primary cause (72%), significantly associated with male gender (p=0.034), lower socioeconomic status (p=0.028), rural habitat (p=0.043), and younger age (mean 30.2±14.5 vs 38.4±18.2 years, p=0.037).Conclusion: Ludwig’s angina predominantly affects young and middle-aged males from rural and lowers socioeconomic backgrounds, with dental infections as the main aetiology. Early recognition of clinical signs and underlying risk factors is essential for effective management.Bangladesh J Otorhinolaryngol 2025; 31(2): 62-68